FERTIGATION SCHEDULING TO SUMMER TOMATO (SOLANUM LYCOPERSICUM COPERSICUM COPERSICUM L.) UNDER PROTECTED CULTIVATION - UGHADE, S. R; TUMBARE, A. D; SURVE, U. S (The Bioscan, 2016)
Among fertigation levels fertigation of 100% RDF recorded significantly maximum growth attributes viz., plant height, number of branches, number of leaflets and leaf area plant-1, yield attributes viz., number of fruits plant1 (74.13, 67.50 and 70.82), fruit weight plant-1 (4.85, 4.43 and 4.64 kg) and tomato fruit yield unit-1 of polyhouse (15.72, 14.07 and 14.90 t) and quality parameters viz., TSS, Titrable acidity, Ascorbic acid, Lycopene content, Carotene content and Pericarp thickness as compared to rest of treatments during both the years and on pooled mean, however at par with 80% RDF. Among the fertigation schedules fertigation of 12 equal splits of NPK at every 9 days interval registered significantly maximum all the growth attributes, yield attributes viz., number of fruits plant-1 (72.54, 66.30 and 69.44), fruit weight plant-1 (4.80, 4.24 and 4.52 kg) and tomato fruit yield unit-1 of polyhouse (15.56, 13.42 and 14.49 t) and quality parameters over rest of treatments during both years and on pooled mean. Based on two years of investigation it concluded that fertigation of 80% RDF in 12 equal splits at every 9 days interval found most suitable to achieve maximum fruit yield and quality of tomato during summer season under polyhouse.